Evaluation of the Motor Function of Sling Exercise Therapy in Children with Cerebral Palsy - Chuntao ZHANG; Zhenhuan LIU; Shangsheng DONG (康复学报)
Objective:To explore the clinical effect of the motor function of sling exercise therapy in children with cerebral palsy.Methods:Forty cases of cerebral palsy were randomly divided into observation group and control group, with 20 cases in each group. Both groups were treated with basic rehabilitation, and sling exercise therapy was added to the observation group. Gross motor assessment scale (GMFM-88), Beijing Gesell scale (Gesell) and Berg balance scale were used to evaluate the motor function before and after trial.Results:The scores of GMFM-88, Gesell and Berg balance scale were improved after trial than those before treatment (P<0.05). After treatment, the scores of the observation group were improved significantly compared to those in the control group (P<0.05).Conclusion:The sling exercise therapy can effectively improve the level of the motor and balance ability of children with cerebral palsy.